Cultural Diversity in Sports: Bridging Gaps and Building Communities - Karimah, Hizbin Nisa; Kumaat, Noortje Anita; Wismanadi, Himawan; Mu’Afi, Hannan Fadjar (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Cultural diversity in sports is a multifaceted phenomenon that encompasses various ethnic, racial, and cultural backgrounds participating in athletic activities. Explores the significance of cultural diversity in sports, highlighting its role in bridging societal gaps and fostering community building. By examining case studies, theoretical frameworks, and empirical research, this paper aims to illustrate how sports can serve as a powerful medium for promoting inclusivity, understanding, and social cohesion. The global landscape of sports has evolved dramatically, reflecting the increasing cultural diversity of societies worldwide. Sports have long been recognized as a unifying force, transcending barriers of language, ethnicity, and socio-economic status. This exploration emphasizes that cultural diversity not only enriches the sporting experience but also plays a crucial role in creating a sense of belonging among individuals from different communities. Ultimately, the manuscript advocates for a deeper understanding of the positive impacts of cultural diversity in sports and the importance of addressing the challenges that accompany it.